Desempenho térmico de cobertura verde utilizando a grama Brachiaria humidicola na cidade de São Carlos-SP - Andrade, Nixon César de (2007)
This work aims to analyze the thermal behavior of a green roof with the Braquiária grass (Brachiaria humidicola), that reaches 1m height, comparing it with a traditional roof (concrete slab on show). Considering temperature and relative humidity data obtained through field measurements in different months, the thermal performance of the green and traditional roofs was analyzed. The inside and outside temperatures, and inside superficial of two test-cells were analyzed. The outside superficial temperatures were estimated through computation program and the solar radiation data and wind speed, necessaries for the use of this program, were provided by the Water Resource and Applied Ecology Center (CRHEA,) and the Engineering School of São Carlos (EESC), both from the University of São Paulo (USP). The results indicate that, submitted to the local climate, the green roof presents optimum performance, particularly for decreasing the temperatures of external and internal roof surfaces. In the same test-cell it was recently realized a similar research, which used the Esmeralda grass (Zoysia japonica), a short vegetation. Comparing the measurement results for cold and hot periods, it was noticed differences between the thermal performance of the two grasses.